The first occurrence of fossil shrimps (Crustacea, Decapoda) in the Ipubi Formation (Lower Cretaceous, Araripe Basin) (Research, Society and Development, 2020)
The Ipubi Formation of the Araripe Basin is an important gypsum reserve whose environment had resulted in the deposition of evaporites with narrow black shale lenses. The objective of the present work was to present the first occurrence of caridean for the dark shale levels of the Ipubi Formation. The specimen collected in the field and analyzed in the laboratory, although not achieving a detailed taxonomic determination, is a very important one because it is the first decapod crustacean found in this formation. We believe the specimen LPU-0918/A and B, is a caridean because of its second abdominal somite having a strongly rounded pleura in the base and it overlaps the first and the third. The knowledge about fossil shrimps is still sparse, and the information presented here can be valuable to the understanding of the evolutive history of the carideans.